Digital Innovation for Economic Growth: An Evaluation of the PAN-G Denbukit Program in Increasing Regional Original Revenue in Buleleng - Kurniawan, Putu Dede; Suwena, Kadek Rai; Irwansyah, M. Rudi (Yayasan Riset dan Pengembangan Intelektual, 2025)
Local Original Income is the income obtained by a region from sources within its own territory which is collected based on regional regulations in accordance with applicable laws and regulations. The purpose of this study is to measure the extent to which the Pan-G Denbukit application can achieve its goals in increasing efficiency and ease of access to regional tax services. The evaluation is also intended to identify the positive impacts given to the community and efforts to improve weaknesses in the implementation of this application. This research method uses an evaluative approach, while data collection is carried out using an instrument in the form of a questionnaire with a semantic differential scale model. The results of this study indicate that the Pan-G Denbukit application is very effective in increasing the efficiency of managing Local Original Income, and is worthy of continued use and further development in order to improve the quality of regional financial management as a whole.